A Unique Source for Innovative Longitudinal Research: The POPLINK Database - Annika Westberg; Elisabeth Engberg; Sören Edvinsson (Historical Life Course Studies)
This paper presents the longitudinal database POPLINK, which has been developed at the Demographic Data Base at Umeå University, Sweden. Based on digitized Swedish population registers between c. 1700-1950, the database contains micro-data that covers the agrarian society through industrialization and further on to the Swedish welfare state and contemporary society. It is now possible to study the profound processes of the second demographic transition using individual level data with a proper size population. POPLINK allows for a large array of longitudinal studies, such as social mobility, migration, fertility, mortality, civil status, kinship relations, diseases, disability and causes of death. International standards of occupations (HISCO) and diseases (ICD-10) have been applied, facilitating comparability. POPLINK covers two large regions in Northern Sweden and is built on complete registrations. It is one of the world’s most information-dense historical population databases, covering up to 15 generations and 350,000 individuals described by 300 variables, allowing the ability to monitor populations over time. POPLINK has been built to allow linkage to modern registries, clinical data and medical biobanks, which enables the study of transgenerational effects, heredity and genetic transfers in disease incidence of the population today. DDB serves as an infrastructure for research and is open to researchers of any nationality.